Dynamical architecture of the HD 107148 planetary system - Eberhardt, Jan; Trifonov, Trifon; Kürster, Martin; Stock, Stephan; Henning, Thomas; Wollbold, Anna; Reffert, Sabine; Lee, Man Hoi; Zechmeister, Mathias; Rodler, Florian; Zakhozhay, Olga; Heeren, Paul; et al. (The astronomical journal, 2022)
We present an independent Doppler validation and dynamical orbital analysis of the two-planet system HD 107148, which was recently announced in Rosenthal et al. Our detailed analyses are based on literature HIRES data and newly obtained HARPS and CARMENES radial-velocity (RV) measurements as part of our survey in search for additional planets around single-planet systems. We perform a periodogram analysis of the available HIRES and HARPS precise RVs and stellar activity indicators. We do not find any apparent correlation between the RV measurements and the stellar activity indicators, thus linking the two strong periodicities to a moderately compact multiplanet system. We carry out orbital fitting analysis by testing various one- and two-planet orbital configurations and studying the posterior probability distribution of the fitted parameters. Our results solidify the existence of a Saturn-mass planet (HD 107148b, discovered first) with a period of P b ∼ 77.2 days and a second, eccentric (e c ∼ 0.4), Neptune-mass exoplanet (HD 107148c) with an orbital period of P c ∼ 18.3 days. Finally, we investigate the two-planet system’s long-term stability and overall orbital dynamics with the posterior distribution of our preferred orbital configuration. Our N-body stability simulations show that the system is long-term stable and exhibits large secular osculations in eccentricity but in no particular mean motion resonance configuration. The HD 107148 system, consisting of a solar-type main-sequence star with two giant planets in a rare configuration, features a common proper-motion white dwarf companion and is therefore a valuable target for understanding the formation and evolution of planetary systems.